SMARTPHONE APPLICATION FOR MEDICAL DATASYNCHRONIZATION ON CLOUD POWERED MIDDLEWARE PATFORM. - BHASIN, SHIV KUMAR; BHANSALI, VISHAL; PETER, J. SELVIN PAUL (Turkish Journal of Physiotherapy Rehabilitation, 2021)
Android application that can be used when minor medical help is needed and doctor is unavailable. This application allows you to manage your health by suggesting medicines, setting reminders (to have water, fix appointment with doctor, take medicine etc.), view exercises and sending a message to your emergency contacts with the location, in situation of critical need. This is achieved by integration of technologies like Cloud, DBMS and GPS and an efficient algorithm that makes the medicine suggestions reliable. It aids in providing overall health and wellness facilities to the user via data stored in the cloud so that it occupies less memory and runs smoothly.